Implementation of Islamic Theological Values In Character Education at SMA Manggala Maruyung Bandung - Yanto Maulana Restu; Mada Sumringah Sari; Nadia Kurnia Fauziah; Andewi Suhartini; Nurwadjah Ahmad (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this study is to analyze and describe how the implementation of Islamic theological values ​​in the formation of student character. This study was conducted at the Manggala Maruyung Senior High School (SMA) Bandung with qualitative case study research in the field. Data sources in this study include observation, documentation, interviews and supplemented with primary data sources and secondary data sources from various reliable references such as scientific journals, books, and other sources that support the study. Data analysis in this study includes steps such as data collection, data presentation, data reduction, and deduction of conclusions. The results of this study indicate that the implementation of Islamic theological values ​​in the curriculum, both the main curriculum and extracurricular, has a positive impact on the formation of good character of students, especially the religious character of students. As in the Manggala Maruyung Senior High School (SMA) Bandung, the Islamic Theology used in the curriculum is based on the theology of Ahlus-As-Sunnah wal Jama'ah with the characteristics of Islamic boarding schools, namely the Tijan ad-Darori book, the Safinah book, the al-banin akhlak book. The book is studied using a classical system as the method in Islamic Boarding Schools, namely using an accent with the meaning of Sundanese pegon and introducing Islamic theology broadly and clearly with the aim of forming the character of students who have strong beliefs and are close to their God wherever and whenever and have a religious personality.